1993
DOI: 10.1021/ma00064a030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal history on the rheological behavior of a thermotropic liquid-crystalline polymer

Abstract: The effect of thermal history on the rheological behavior of a thermotropic liquid-crystalline polymer was investigated. For the study, an aromatic polyester, poly[(phenylsulfonyl)-p-phenylene-l,10decamethylenebis(4-oxybenzoate)] (PSHQ10), was synthesized. PSHQ10 was found to have (a) a weightaverage molecular weight of 35 000 relative to polystyrene standards and the polydispersity index of 2.0, (b) a glass transition temperature of 80 °C, (c) a melting point of 110 °C, and (d) a nematic-isotropic transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…These crystals are metastable and the formation is highly dependent on annealing conditions: temperature and time. Han et al 15 and Kim and Han 16 also found an intermediate melting endotherm before normal melting in poly[(phenylsulfonyl)-p-phenylene 1,10-decamethylene bis-(4-oxybenzoate)] (PSHQ10) caused by annealing; the formation of this annealing-induced endotherm has a profound effect on the rheological properties of this polymer.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These crystals are metastable and the formation is highly dependent on annealing conditions: temperature and time. Han et al 15 and Kim and Han 16 also found an intermediate melting endotherm before normal melting in poly[(phenylsulfonyl)-p-phenylene 1,10-decamethylene bis-(4-oxybenzoate)] (PSHQ10) caused by annealing; the formation of this annealing-induced endotherm has a profound effect on the rheological properties of this polymer.…”
Section: Introductionmentioning
confidence: 94%
“…The double or multimelting phenomenon has long been observed in a number of crystalline polymers, such as flexible chain, semirigid chain, and rigid chain polymers: for instance, polyethylene (PE), 3 polypropylene (PP), 4 nylon, 5 poly(ethylene terephthalate) (PET), 6,7 poly(aryl ether ether ketone) (PEEK), 8 -10 poly(ether diphenyl ether ketone) (PEDEK), 11 and thermotropic liquid crystalline polyesters. [12][13][14][15][16][17][18] Among those polymers PET and PEEK have been extensively studied by a number of authors. A variety of explanations for the multimelting behavior have been put forward: (1) different crystal structures, which have been observed in trans-1,4-polyisoprene, 19 isotactic polypropylene 4 ; (2) different morphological characters with different lamellar thicknesses, which have been found in cis-1,4-polyisoprene 20 and PEEK; and (3) melting, reorganization, and remelting, which were observed in poly(⑀-caprolectone), 21 and PET.…”
Section: Introductionmentioning
confidence: 99%
“…So, we consider that thermal history also has a certain effect on the difference between figure 6 and figure 8. Seung Su Kim [74] and M. L. Cerrada [75] have studied the effect of thermal history on the phase behavior of polymeric materials, and it showed that some contradictory results in the references are likely to be caused by the different thermal history of a sample.…”
Section: -8mentioning
confidence: 99%
“…As demonstrated previously, [13][14][15][16] the initial morphology of a TLCP specimen can be controlled by heating the specimen above its clearing temperature (T NI ), shearing in the isotropic phase, and then cooling to a predetermined temperature in the anisotropic state. Such practice is only possible for TLCPs with T NI lower than the thermal degradation temperature.…”
Section: Introductionmentioning
confidence: 99%